2022
DOI: 10.1039/d2an00355d
|View full text |Cite
|
Sign up to set email alerts
|

Imaging mass spectrometry differentiates the effects of doxorubicin formulations on non-targeted tissues

Abstract: Imaging mass spectrometry indicated a wide range of chemical disturbances in a model of non-targeted organs of rats treated with different formulations of doxorubicin and enabled the differentiation of drug formulation-specific effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In our previous study conducted on the kidneys of DOX-treated rats, we have shown that the use of MSI analysis can provide a wide variety of information for the safety profiling of drug formulations. 38 Here, we decided to focus on the metabolic and lipidomic markers involved in DOX-induced cytotoxicity and cellular response, namely spermine, Car, Cer, and LysoPC. An overview of their biological effects related to DOX toxic effects and their tentative annotations are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study conducted on the kidneys of DOX-treated rats, we have shown that the use of MSI analysis can provide a wide variety of information for the safety profiling of drug formulations. 38 Here, we decided to focus on the metabolic and lipidomic markers involved in DOX-induced cytotoxicity and cellular response, namely spermine, Car, Cer, and LysoPC. An overview of their biological effects related to DOX toxic effects and their tentative annotations are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of lipoDOX and PLGADOX formulations was done as described previously by means of their shape, size, and size distribution, as well as surface charge after dilution with saline solution (see ESI †). 38…”
Section: Drug Formulationsmentioning
confidence: 99%